Institutions and the management of human resources: incentive pay systems in France and Great Britain - Marsden, David; Belfield, Richard (London, 2009)
"Using data from large-scale establishment surveys in Britain and France, we show that incentive pay for non-managers is more widespread in France than in Britain. We explain this finding in terms of the ‘beneficial constraint’ arising from stronger employment protection in France, which provides an impulse to develop incentive pay; employer networking activities in France, which facilitate joint learning about its development and operation; and government fiscal incentives for profit-sharing, which reduces the cost of its operation. "